The status of epidermal growth factor receptor and topoisomerase IIα genes in triple-negative breast cancer cells - D. A. Karseladze; I. V. Poddubnaya; A. I. Karseladze (Опухоли женской репродуктивной системы, 2014)
The paper gives the results of studying the genes of epidermal growth factor receptor (EGFR) and topoisomerase IIα (TOP IIα) in patients with triple-negative breast cancer (BC). It is suggested that the lack of EGFR gene amplification might serve as a factor of good prognosis. TOP IIα gene amplification usually occurs in the tumors responsive to chemotherapy including anthracycline drugs. The altered status of the above genes should be interpreted in the context of aneusomy of chromosomes 7 and 17, on which they are located. No association was found between the pattern of EGFR and TOP IIα gene abnormalities and the basaloid phenotype of BC.